Everyday courage : the lives and stories of urban teenagers - Way, Niobe, 1963- (Qualitative studies in psychology., 1998)
What does it mean to be a teenager in an American city at the close of the twentieth century? How do urban surroundings affect the ways in which teens grow up, and what do their stories tell us about human development? In particular, how do the negative images of themselves on television and in the newspaper affect their perspectives about themselves? Psychologists typically have shown little interest in urban youth, preferring instead to generalize about adolescent development from studies of their middle-class, suburban counterparts. In Everyday Courage Niobe Way, a developmental psychologis.